Mendalami Kesiapan UMKM dan Relevansi SAK EMKM Di Era Industri 4.0 - Dwijayanti, Ni Made Ayu; Karmana , I Wayan; Trisnadewi, Ketut Sinta (Politeknik Ganesha Medan, 2024)
This study aims to explore the readiness of Rose Madani MSMEs in implementing the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) and the relevance of preparing financial reports according to SAK EMKM standards in the Industrial Era 4.0. This study uses a qualitative descriptive approach where the readiness of Rose Madani MSMEs is assessed by 3 aspects, namely HR readiness, supporting applications, and MSME commitment. The results of the study indicate that Rose Madhani MSMEs are not ready to implement SAK EMKM. The low level of accounting understanding is an obstacle from the HR aspect, the absence of a digital application based on SAK EMKM is an obstacle from the infrastructure side, and the perception of MSME owners that consistent financial recording is not important in managing MSMEs is an aspect that causes low commitment to implementing SAK EMKM. The implementation of financial reports in accordance with SAK EMKM presents financial reports consisting of three components, namely financial position reports, several statistics, and financial report notes. Digitalization of MSME financial reports based on SAK EMKM can increase efficiency and reduce operational costs at Rose Madani MSMEs. Utilizing software in accordance with SAK EMKM standards in financial preparation can provide more accurate, effective, and efficient financial data and reports in accordance with applicable standards..